Seeing through Zen encounter, transformation, and genealogy in Chinese Chan buddhism - McRae, John R. 1947-2011 (Univ. of California Press, 2003)
Using modern critical techniques, supported by recent manuscript discoveries, John McRae shows how a skeptical, accurate & productive assessment of Chan lineages may be made. He offers new, accessible analytic models for the interpretation of Chan spiritual practices & religious history.
Includes bibliographical references and index
Keywords: Bouddhisme zen - Chine - Histoire; Geschichte; Zen Buddhism -- China -- History; Zen-Buddhismus; China